Successful treatment of giant basal cell carcinoma with topical imiquimod 5% cream with long term follow-up - M Chun-Guang; L Qi-Man; Z H Yu-Yun; C H Li-Hua; Tiffany Cheng; H Jian-De (Wolters Kluwer Medknow Publications, 2014)
The use of the topical Imiquimod 5% cream offers a noninvasive, nonsurgical, and an effective option for the treatment of primary small (<2 cm) superﬁcial basal cell carcinoma (sBCC). However, reports about successful treatment of giant (>5 cm) BCC with topical Imiquimod 5% cream are rare. We present our experience in the treatment of two giant tumors (6 × 8 cm 2 , 5.2 × 4.2 cm 2 ) of BCC on the face with Imiquimod 5% cream, 2 to 3 days/week for 12 weeks. Both the tumors were cured with clinical and pathological evidence, one with 6-year follow-up and the other with 3.5-year follow-up.